2015
DOI: 10.1093/pubmed/fdv013
|View full text |Cite
|
Sign up to set email alerts
|

Childhood idols, shifting from superheroes to public health heroes

Abstract: It is early Saturday morning: a day for heroes. Bogged down with various costumes, capes and action figures, young Nikoli bounds downstairs to catch reruns of Teen Titans He puts his newly acquired reading skills to work, studying comic books and recreating the adventures therein. Nikoli imagines himself as the hero in his comics, defeating villains and saving victims, imitating the poses and catchphrases in the mirror. Although children like Nikoli will never gain super strength or the ability to fly, the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The Elaboration Probability Model 46 used in the last stage refers to results that different persuasion variables have on the change process and in the strength of these results 46 . Superheroes have a high impact power in the real life of children, who can idealize their growth, thinking of being like the hero they most admire 66 . Comic superheroes have played important roles promoting health in various fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Elaboration Probability Model 46 used in the last stage refers to results that different persuasion variables have on the change process and in the strength of these results 46 . Superheroes have a high impact power in the real life of children, who can idealize their growth, thinking of being like the hero they most admire 66 . Comic superheroes have played important roles promoting health in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…Comic superheroes have played important roles promoting health in various fields. Their interventions in the area of epidemiology, education, and psychology have been reported 66 . The use of heroic characters in the history of video games, aiming at promoting health for children, is a strategy that has been used 23 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…and Brown et al . have argued in the case of science and public health comics, respectively, comics can enable non‐specialists to engage with complex topics …”
Section: Discussionmentioning
confidence: 99%
“…Some literature has an entirely positive view: the construction of heroes in films, comics and television, for example, may encourage young people and children into decidedly altruistic future roles. Indeed, it has even been suggested that putting health care personnel on the same level as superheroes such as Superman, could conceivably lead to a realignment of children's idols, and in turn encourage them towards saving lives through education, treatment and research in adulthood (Brown et al 2016). Anxieties associated with the visualisation of graphic or depressing disease symptoms might also be contained or moderated by weaving plots around heroic medical figures (Tomes 2002, 646).…”
Section: Articlementioning
confidence: 99%